2012
DOI: 10.1108/00346651211228496
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic response to amylopectin rich starch present in common fasting foods of India

Abstract: PurposeStarchy foods have been emphasized in the diet for reducing hyperglycemia and hyperinsulinemia. However, all starch containing foods respond differently, depending upon various other factors in food such as the amylose:amylopectin ratio, co‐ingredients, methods of cooking, etc. which also impact its metabolic response. During days of fast, in India, potato and sago are the most commonly used food to provide quick source of energy. The purpose of this paper is to determine the functional and nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It has been shown that sago had a lower glycemic index value (40.7, low level) (Wahjuningsih et al, 2016) compared to the other staple foods, for instance, white rice (61-87, medium to high level) and sweet potato (77, medium) (Osman et al, 2021). Other studies reported the values of sago glycemic index using different settings were 27 (Haliza et al, 2006) and 33 bread equivalent per 100 g (Singhania & Senray, 2012). However, the three commonly used glycemic index categories may be incorrectly assigned to foods due to variations in GI methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that sago had a lower glycemic index value (40.7, low level) (Wahjuningsih et al, 2016) compared to the other staple foods, for instance, white rice (61-87, medium to high level) and sweet potato (77, medium) (Osman et al, 2021). Other studies reported the values of sago glycemic index using different settings were 27 (Haliza et al, 2006) and 33 bread equivalent per 100 g (Singhania & Senray, 2012). However, the three commonly used glycemic index categories may be incorrectly assigned to foods due to variations in GI methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, sago could be an option as a food or supplement for athletes or people in physical exercise to maintain performance and accelerate recovery. It could be due to starch-based foods that are high amylopectin content (e.g., sago and potatoes) speeding up the absorption of sugar, supplying the cells' need for energy Immediately (Singhania & Senray, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, black beans also had the lowest calorie per gram compared to other variants of Lablab beans (table 1). A food source with high amylopectin induces a better glycemic response, especially during fasting (Singhania & Senray 2012). This starch also provides higher energy intake than low amylopectin sources (Singhania & Senray 2012).…”
mentioning
confidence: 99%
“…A food source with high amylopectin induces a better glycemic response, especially during fasting (Singhania & Senray 2012). This starch also provides higher energy intake than low amylopectin sources (Singhania & Senray 2012). Moreover, the increasing ratio of amylopectin/amylose reflects better nutrient digestibility (Gao et al 2020).…”
mentioning
confidence: 99%